Snow sports equipment: Current developments for improved protection and prevention - Senner, V. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Even though there is no doubt that snow sport is contributing to well being and health, its inherent risks cannot be overseen: the injury rate per 1000 skier days is between 1.9 and 3.5 (Brügger et al., 2010) and with approx. 350 million skier days worldwide (Venant, 2010) we count for a total of 665,000 to 1.2 million snow sport injuries. Every endeavor therefore has to be made to improve protection and prevention. After giving some statements and current findings as presented at the 18th ISSS-Congress 2009 on Skiing Safety the keynote will take a look at technological measures that may have the potential to increase snow sport safety.